The Development of the Tarekat among the Madurese Population until the Beginning of the 20th Century - Iswahyudi (Britain International for Academic Research (BIAR) Publisher, 2021)
In its development, the number of tarekat found in Madura was three, namely the tarekat Qadiriyah, the tarekat Qadiriyah Wa Naqshabandiyah, and the tarekat Tijaniyah. In addition, the tarekat Syatariyah, which had a lot of contact with the traditions of the local Madurese community, had also been influential, even though it was not so big. In this case it is known that starting from the development of the performing arts among the Madurese population called rateb, or from the Arabic language ratib which is similar to the debus performances in Banten and Aceh, there is a strong suspicion that the tarekat Samaniyah has also developed in Madura since the 18th century. In its journey, the popularity of the tarekat Sammaniyah, especially in Madura, was replaced by the Qadariyah wa Naqsabandiyah. This tarekat in its development has replaced the fame of the tarekat Sammaniyah in the archipelago. The description from the sketch shows that in reality, we are often faced with local Islamic sketches, in the form of rituals, such as tarekat, tahlilan, salvation, and so on. The approaches used to telescope this are textual-contextual and structural-functional approaches. From the analysis, it is found that the patterns of understanding and attitudes of the majority of rural communities, especially Madurese, practice Islamic teachings in the form of rituals that are independent, walk alone, without recognizing the relationship between students and sheikhs or murshids.